Scintigraphic imaging of pituitary adenomas: An in vivo evaluation of somatostatin receptors - Oppizzi, G.; Cozzi, R.; Dallabonzana, D.; Orlandi, R.; Benini, Z.; Petroncini, M.; Attanasio, R.; Milella, M.; Banfi, G.; Possa, M. (Journal of endocrinological investigation, 1998)
We have performed pituitary scintigraphy with the somatostatin (SS) analog pentetreotidean by (111In-P) in patients with GH-secreting adenoma or with "clinically non functioning" adenoma (NFA) to evaluate the presence and the functionality of SS receptors (SS-R). 111In-P pituitary accumulation was expressed as Activity Ratio (AR): the ratio between the uptake of radioactivity by the adenoma and that of the normal brain tissue. In subjects without pituitary disease, AR ranged from 1.6 to 2.2 and a value lower than 2.2 was thus arbitrarily considered as normal. In 15 out of the 17 patients with GH-secreting adenoma, an accumulation of the radioligand was shown. Median AR was 3.8 (range 1-6.9; in 14 AR were greater that 2.2) and ARs were directly correlated (r = 0.54; p < 0.05) with the suppressibility of plasma GH levels by octreotide (OC) acute administration. In two patients who repeated scintigraphy during chronic OC treatment, AR values were reduced. In all the 22 patients with NFA an accumulation of 111In-P at the pituitary level was observed and median AR was 3.0 (range 1.5-20; in 14 greater that 2.2). In vitro autoradiography of surgical specimens in 6 NFA patients revealed SS-R in 4 cases with high scintigraphic AR and negative results in two cases with low AR. Scintiscan was repeated during chronic OC treatment in 5 patients with high score: AR decreased in one patient, increased in three, and did not change in the other patient. No changes in tumor size were shown in any of these patients. A total of 8 patients (3 GH secreting and 5 NFA) had "normal" AR values. In acromegaly scintigraphy with 111In-P visualizes functioning pituitary SS-R coupled to intracellular events that control hormonal hypersecretion and tumor growth. In contrast, in spite of the positivity of 111In-P imaging in most patients with NFA, their receptors might have a defect in the coupling-transduction process, as they are not inhibited by OC treatment and no tumor shrinkage is observed.